The Relationship Between Government Expenditure and Regional Economic Growth: Evidence from Indonesia - Lakat, Junior Semuel; Kumenaung, Anderson Guntur; Lengkong, Victor Paskah Kalawat; Gamaliel, Hendrik (Klabat Accounting Review; Vol 6 No 1 (2025): Klabat Accounting ReviewDO - 10.60090/kar.v6i1.1217.24-35, 2025)
This study investigates the relationship between government expenditure and regional economic growth in Indonesia, focusing on its impact on per capita income and Gross Regional Domestic Product (GRDP). Utilizing a comprehensive panel data analysis across 508 regencies/cities from 2018 to 2022, the study employs Fixed Effect Model (FEM) to account for regional heterogeneity. The findings reveal that Personnel and Goods and Services Expenditures significantly enhance both per capita income and GRDP, while Capital Expenditure negatively impacts these economic outcomes, potentially due to the delayed returns of infrastructure investments. Interest Payments show a positive effect on per capita income, suggesting that efficient debt management may bolster economic performance. However, expenditures on subsidies, grants, and social assistance exhibit inconsistent impacts, indicating potential inefficiencies in resource allocation. This research provides critical insights for policymakers in optimizing public expenditure to foster equitable regional development and sustainable economic growth.